Short-Term Postpartum Blood Pressure Self-Management and Long-Term Blood Pressure Control: A Randomized Controlled Trial - Kitt, Jamie A.; Fox, Rachael L.; Cairns, Alexandra E.; Mollison, Jill; Burchert, Holger H.; Kenworthy, Yvonne; McCourt, Annabelle; Suriano, Katie; Lewandowski, Adam J.; Mackillop, Lucy; Tucker, Katherine L.; McManus, Richard J.; et al. (Hypertension (Dallas, Tex. 1979), 2021)
Women with hypertensive pregnancies are 4× more likely to develop chronic hypertension. Previously, we showed a short period of blood pressure (BP) self-management following hypertensive pregnancy resulted in persistently lower BP after 6 months. We now report the impact on long-term BP control. Women who participated in the postpartum randomized controlled trial, SNAP-HT (Self-Management of Postnatal Hypertension; NCT02333240), were invited for 24-hour ambulatory and clinic BP measures. Height and weight were measured by calibrated scales and standardized tape measures, activity by 7-day wrist-worn accelerometer, and dietary factors assessed by questionnaire. Sixty-one of 70 eligible women were followed up 3.6±0.4 years after their original pregnancy. Twenty-four–hour diastolic BP was 7.0 mm Hg lower in those originally randomized to postpartum BP self-management instead of usual care. This difference remained significant after adjustment for either BP at the time of delivery (−7.4 mm Hg [95% CI, −10.7 to −4.2]; P <0.001) or pregnancy booking BP (−6.9 mm Hg [95% CI, −10.3 to −3.6]; P <0.001). Adjustment for current salt intake, age, body mass index, waist-to-hip ratio, arm circumference, parity, alcohol intake, and physical activity had no effect on this difference. Reductions in diastolic BP at 6 months, following self-management of BP postpartum, are maintained 3.6 years later as measured by lower 24-hour diastolic BP. Interventions to optimize BP control during the puerperium in women with hypertensive pregnancies improve BP in the longer term, in a cohort at increased risk of developing chronic hypertension and major adverse cardiovascular events.